2021
DOI: 10.3390/pathophysiology28020020
|View full text |Cite
|
Sign up to set email alerts
|

The Angiotensin-Converting Enzyme Inhibitor Lisinopril Mitigates Memory and Motor Deficits in a Drosophila Model of Alzheimer’s Disease

Abstract: The use of angiotensin-converting enzyme inhibitors (ACEis) has been reported to reduce symptoms of cognitive decline in patients with Alzheimer’s disease (AD). Yet, the protective role of ACEis against AD symptoms is still controversial. Here, we aimed at determining whether oral treatment with the ACEi lisinopril has beneficial effects on cognitive and physical functions in a Drosophila melanogaster model of AD that overexpresses the human amyloid precursor protein and the human β-site APP-cleaving enzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 66 publications
(87 reference statements)
1
10
0
Order By: Relevance
“…141 Another recent study also conducted in Drosophila that overexpressed APP and the human β-site APP-cleaving enzyme (BACE) in neurons, demonstrated that treatment of AD flies with the ACEI Isinopril improved learning and memory deficits on the aversive phototaxic suppression assay and reduced ROS levels. 142 Although ACEIs have been found to exhibit beneficial effects on AD pathology, some studies have demonstrated detrimental effects of ACEIs, with the main concern being that the ACE is capable of cleaving Aβ peptides into less aggregable species, thus its inhibition may actually lead to enhanced Aβ deposition. 143 This was demonstrated in APP Swedish transgenic mice treated with ACEI, captopril, resulting in increased cerebral Aβ deposition.…”
Section: 83mentioning
confidence: 99%
See 1 more Smart Citation
“…141 Another recent study also conducted in Drosophila that overexpressed APP and the human β-site APP-cleaving enzyme (BACE) in neurons, demonstrated that treatment of AD flies with the ACEI Isinopril improved learning and memory deficits on the aversive phototaxic suppression assay and reduced ROS levels. 142 Although ACEIs have been found to exhibit beneficial effects on AD pathology, some studies have demonstrated detrimental effects of ACEIs, with the main concern being that the ACE is capable of cleaving Aβ peptides into less aggregable species, thus its inhibition may actually lead to enhanced Aβ deposition. 143 This was demonstrated in APP Swedish transgenic mice treated with ACEI, captopril, resulting in increased cerebral Aβ deposition.…”
Section: 83mentioning
confidence: 99%
“…Treatment with captopril decreased cerebral cell death and demonstrated an ability to rescue memory deficits also in a Drosophila model expressing the Aβ42 transgene, but this trend was not seen in flies expressing human tau, suggesting that ACEIs may work through targeting Aβ pathology 141 . Another recent study also conducted in Drosophila that overexpressed APP and the human β‐site APP‐cleaving enzyme (BACE) in neurons, demonstrated that treatment of AD flies with the ACEI Isinopril improved learning and memory deficits on the aversive phototaxic suppression assay and reduced ROS levels 142 . Although ACEIs have been found to exhibit beneficial effects on AD pathology, some studies have demonstrated detrimental effects of ACEIs, with the main concern being that the ACE is capable of cleaving Aβ peptides into less aggregable species, thus its inhibition may actually lead to enhanced Aβ deposition 143 .…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila is a powerful organism for modeling human disease, including neuromuscular disorders [ 107 , 108 , 109 , 110 , 111 , 112 , 113 ]. Such models have provided novel insights into disease mechanisms and identified potential drug targets and treatments [ 64 , 113 , 114 , 115 , 116 , 117 , 118 ]. In addition, Drosophila is one of a few selected model organisms used by the Undiagnosed Disease Network (UDN) to functionally test DNA sequence variants of uncertain significance in candidate disease genes ( ).…”
Section: Discussionmentioning
confidence: 99%
“…The density of these neurofibrillary aggregates in the neocortex correlates with dementia (Wang et al, 2013). This could be potentially inhibited by employing a centrally acting ACEi, which has been demonstrated to mitigate memory deficits, as demonstrated in different experimental AD models, mainly by reducing inflammation and/ or reactive oxygen species levels (AbdAlla et al, 2013;Thomas et al, 2021;Torika et al, 2016), and is consistent with known dysregulation of redox in AD (Holubiec et al, 2022). This approach has also been investigated in patients, showing that a brainpenetrating ACEi can counteract the process of neurodegeneration and dementia (Quitterer & AbdAlla, 2020).…”
Section: Roles Of Ace and Ace2 In Neurodegenerative Diseasesmentioning
confidence: 99%